A Literacy Program in Increasing of Reading Interest and Children Creativity at Tempurejo Village by Collaborative KKN 045 Jember - Zahroh, Millatuz; Ahmad Pujiono; Ayuri Wahyu; Dhea Maulana; Andriani; Indri Ariestiana (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
The Collaborative Real Work Lecture Program (KKN-K) is a form of activity carried out to provide students with learning experiences in social life so that they can help local communities and villages. The KKN-K activities carried out by KKN-K 045 students have a literacy theme called 'Gemilang' or the Inspiring Reading Movement and Brilliant Literacy. The aim of establishing Gemilang activities is to increase interest in reading and foster creativity for the children of Tempurejo Village. This literacy activity was carried out in three places, namely MI Miftahul Ulum, Al-Muna Civilization House, and TPQ Izzatul Qur'an, Tempurejo Village, Jember Regency. The method used during the activity was field observation. Through literacy development activities for the children of Tempurejo Village, especially kindergarten and elementary school age, it is hoped that this will increase their interest in reading and develop children's creativity.